Changes in Acetyl CoA Levels during the Early Embryonic Development of Xenopus laevis - Tsuchiya, Yugo; Pham, Uyen; Hu, Wanzhou; Ohnuma, Shin-ichi; Gout, Ivan (PLOS ONE, 2014)
Coenzyme A (CoA) is a ubiquitous and fundamental intracellular cofactor. CoA acts as a carrier of metabolically important carboxylic acids in the form of CoA thioesters and is an obligatory component of a multitude of catabolic and anabolic reactions. Acetyl CoA is a CoA thioester derived from catabolism of all major carbon fuels. This metabolite is at a metabolic crossroads, either being further metabolised as an energy source or used as a building block for biosynthesis of lipids and cholesterol. In addition, acetyl CoA serves as the acetyl donor in protein acetylation reactions, linking metabolism to protein post-translational modifications. Recent studies in yeast and cultured mammalian cells have suggested that the intracellular level of acetyl CoA may play a role in the regulation of cell growth, proliferation and apoptosis, by affecting protein acetylation reactions. Yet, how the levels of this metabolite change in vivo during the development of a vertebrate is not known. We measured levels of acetyl CoA, free CoA and total short chain CoA esters during the early embryonic development of Xenopus laevis using HPLC. Acetyl CoA and total short chain CoA esters start to increase around midblastula transition (MBT) and continue to increase through stages of gastrulation, neurulation and early organogenesis. Pre-MBT embryos contain more free CoA relative to acetyl CoA but there is a shift in the ratio of acetyl CoA to CoA after MBT, suggesting a metabolic transition that results in net accumulation of acetyl CoA. At the whole-embryo level, there is an apparent correlation between the levels of acetyl CoA and levels of acetylation of a number of proteins including histones H3 and H2B. This suggests the level of acetyl CoA may be a factor, which determines the degree of acetylation of these proteins, hence may play a role in the regulation of embryogenesis.